2015
DOI: 10.1111/nph.13749
|View full text |Cite
|
Sign up to set email alerts
|

Macroevolution of leaf defenses and secondary metabolites across the genus Helianthus

Abstract: SummaryLeaf defenses are widely recognized as key adaptations and drivers of plant evolution. Across environmentally diverse habitats, the macroevolution of leaf defenses can be predicted by the univariate trade-off model, which predicts that defenses are functionally redundant and thus trade off, and the resource availability hypothesis, which predicts that defense investment is determined by inherent growth rate and that higher defense will evolve in lower resource environments.Here, we examined the evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 117 publications
(197 reference statements)
2
56
3
Order By: Relevance
“…A recent phylogenetic analysis of sunflowers found that species with more resource-conservative traits were more defended, although this was apparently not driven by light or other aspects of the resource environment (Mason et al 2016). A recent phylogenetic analysis of sunflowers found that species with more resource-conservative traits were more defended, although this was apparently not driven by light or other aspects of the resource environment (Mason et al 2016).…”
Section: P Erspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phylogenetic analysis of sunflowers found that species with more resource-conservative traits were more defended, although this was apparently not driven by light or other aspects of the resource environment (Mason et al 2016). A recent phylogenetic analysis of sunflowers found that species with more resource-conservative traits were more defended, although this was apparently not driven by light or other aspects of the resource environment (Mason et al 2016).…”
Section: P Erspectivesmentioning
confidence: 99%
“…Here the relationship between leaf mass per area (all X axes) is shown against leaf nitrogen (column 1), trichome density (column 2), and defensive cardenolides (column 3) at each scale. 2 LES framework, and one study of sunflowers found trichome density to be unrelated to LES traits (Mason et al 2016). [Color figure can be viewed at wileyonlinelibra ry.com] Article e02924; page 18 ANURAG A. AGRAWAL Ecology,Vol.…”
Section: Leaf Economics and Defense In The Milkweedsmentioning
confidence: 99%
“…Focused studies of tropical tree genera have found that congeneric species are often remarkably divergent in secondary metabolites (Becerra 1997, Kursar et al 2009, Fine et al 2013, Richards et al 2015, Salazar et al 2016. However, few studies have pursued untargeted metabolomics in a community or evolutionary context (Macel et al 2014, Richards et al 2015, Mason et al 2016) and none has examined interspecific metabolomic variation in a forest at the community scale.…”
Section: Introductionmentioning
confidence: 99%
“…Plants initiate the essential and secondary metabolism response of various plant pathogen associations and their immediate involvement in response to various pathogenic attacks cannot be denied (Mason et al, 2016). Among various essential metabolites, the regulation of amino acids has a particular role in plant resistance (Waqas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%